PENGARUH KOMITMEN ORGANISASI, PROMOSI JABATAN, DAN KEDISIPLINAN KERJA TERHADAP KINERJA KARYAWAN PADA GRIYA HOTEL MEDAN - Simangunsong, Elisabeth; Pasaribu, Sasputra; Haloho, Elizabeth; Purba, Imelda; Sagala, Roslinda (LPPM Universitas Katolik Santo Thomas Medan, 2024)
The purpose of this research is to determine the influence of organizational commitment, promotion and work discipline on employee performance at Giya Hotel Medan. The analytical method used is multiple linear regression with data processing using the SPSS 25 program. Data collection was carried out by distributing questionnaires to 43 employees at Griya Hotel Medan. Data testing techniques used in this research include validity and reliability tests, multiple linear regression analysis and hypothesis testing with t and F tests. The results of research using the t test show that partially there is a positive and significant influence of commitment, promotion, work discipline on employee performance. The results of the F test show that simultaneously there is a significant influence of the variables organizational commitment, promotion and work discipline on employee performance. The coefficient of determination (R Square) is 0.699. This means that variations in employee performance can be explained by variations in organizational commitment, promotion and work discipline by 69.9%, while another 30.1% is explained by other factors not explained in this research.